Analysis of Mechanically Activated Ion Channels at the Cell-Substrate Interface: Combining Pillar Arrays and Whole-Cell Patch-Clamp - Sianati, Setareh; Kurumlian, Anie; Bailey, Evan; Poole, Kate (Frontiers in Bioengineering and Biotechnology, 2019)
Ionic currents can be evoked by mechanical inputs applied directly at the cell-substrate interface. These ionic currents are mediated by mechanically activated ion channels, where the open probability increases with increasing mechanical input. In order to study mechanically activated ion channels directly at the interface between cells and their environment, we have developed a technique to simultaneously monitor ion channel activity whilst stimuli are applied via displacement of cell-substrate contacts. This technique utilizes whole-cell patch-clamp electrophysiology and elastomeric pillar arrays, it is quantitative and appropriate for studying channels that respond to stimuli that are propagated to an adherent cell via the physical substrate. The mammalian channels PIEZO1, PIEZO2 and TRPV4 have been shown to be activated by substrate deflections that mimic the magnitude of physical stimuli that impact cells in situ.